Advancing special needs oral healthcare in Southeast Asia through Taiwan's New South Bound Project: Institutional feedback and sustainable strategies - Chia-Tze Kao; Tsui-Hsien Huang; Ming-Yi Lu; Chuan-Hang Yu (Journal of Dental Sciences, 2025)
Background/purpose: Providing oral healthcare to individuals with special needs remains inadequate in Southeast Asia. This study evaluated the outcomes from five universities across three Southeast Asian countries participating in Taiwan's “New South Bound Special Needs Patients Oral Care Project” after its four-year implementation (2018–2021). Materials and methods: The questionnaires distributed to participating universities collected data on dental professionals' demographics, patient characteristics, and project satisfaction. Descriptive statistics analyzed the responses. Results: All universities reported excellent satisfaction with the project. Dental professionals’ ages ranged from 31 to 60 years, and their service experience varied from 1 to 10 years. Special needs patients receiving dental care ranged from <5 % to 30 %, predominantly from urban areas, with most universities serving older adults. Each institution developed unique education, outreach, and institutional collaboration promotion strategies. Conclusion: The project successfully established special needs oral health programs with high satisfaction levels. It facilitated knowledge transfer, including Taiwan's expertise in domiciliary dental care. Recommendations include expanding collaboration, developing standardized curricula, implementing caregiver education, establishing monitoring systems, creating a regional network, and expanding domiciliary care training. These efforts align with WHO's Sustainable Development Goals while improving oral healthcare accessibility for individuals with special needs.